Lymphocytes Subpopulation in Peripheral Blood and Spleen of Village Chickens Recognized by Monoclonal Antibodies (SUBPOPULASI LIMFOSIT PADA DARAH TEPI DAN LIMPA AYAM KAMPUNG YANG DIKENALI OLEH ANTIBODI MONOCLONAL) - Astawa, Nyoman Mantik; Oka, Ida Bagus Made (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Lymphocytes play important role in host defence system against pathogenic agents both in mammalianand avian species. Monoclonal antibodies (mAbs) have been widely used to identify lymphocytessubpopulation in a host based on their surface cluster differentiation (CD) markers. Currently, mAbsagainst lymphocytes surface markers of village chickens have been produced by fusion of myeloma withlymphocytes derived from spleen of mice immune to chicken lymphocytes. In two fusion experiments, 623clones of hybridomas were produced and four (BG4, CB1, DB2 and BB2) of which secreted mAbs againstchickens lymphocyte surface molecules. Two mAbs (BG4 and DB2) recognized protein of 32 kDa, one mAb(CB1) recognized protein of 64 kDa, and one mAb was unable to recognize any protein of chicken lymphocytesurface molecule. Three mAbs recognized lymphocyte subpopulation in spleen and peripheral blood ofvillage chickens. In peripheral blood, mAbs BG4, CB1 and DB2 recognized lymphocytes subpopulationwith the percentages of 11.2%, 21.4% and 7.4% respectively. In spleen those three mAbs recognizedlymphocytes subpopulations at the percentages of 38.2%, 51.54% and 31.5% respectively. Based on thoseresult, it is very likely that mAbs BG4 and DB2 recognized CD4 molecule and mAb CB1 recognized CD8molecule of village chickens lymphocytes.
Keywords: CD8+; CD4+; lymphocytes; chickens; monoclonal; antibodies